An examination of large-scale electronic health records implementation in Primary Healthcare Centers in Saudi Arabia: a qualitative study - Alzghaibi, Haitham A. (Frontiers in Public Health, 2023)
Introduction: Digital transformation has become a buzzword in almost every industry in the 21st century. Healthcare is not an exception. In the healthcare industry, digital transformation includes the utilization of electronic health records (EHRs), telemedicine, health information exchange, mobile health, and other interactive platforms. The importance of digital transformation in healthcare cannot be overemphasized as it has proven to be critical in improving patient outcomes, making healthcare delivery more efficient, and reducing costs. The positive impact of electronic health records was noticed almost immediately in the field of primary healthcare. It has been suggested that implementing electronic health records will enhance the accessibility and the process of distribution of health records between authorised users. As part of Saudi vision 2030, all healthcare organisations in Saudi Arabia are going to shift to digital transformation. Methods: this study follows qualitative, semi-structure, face to face interviews approach. The collected data were analysed using NVivo V10. Inductive thematic analysis approach was used to analyse the collected data from the interviews. Result: Seventeen project team members, from different position and different background were purposively chosen to be interviewed. Three main themes and 38 codes were generated from the analysis of transcripts. The informants describe the implementation of electronic health records in the PHCs based on two different experiences. The participants reported that a previous attempt failed due to inappropriate infrastructure, lack of technical support and law level of user acceptance. Therefore, the policy makers adopted several steps to increase the level of success and avoid failure causes. They initially establish well defined request for proposal followed by continues commendation among project team and conduct consultation on multiple level (country level; organizational level and individual level). Conclusion: this study concluded that the main causes that lead to the failure of the large-scale project were lack of connectivity, lack of technical support, and staff changes, particularly those who occupied high level positions in the Saudi ministry of Health. The success rate of EHRs implementation can be directly impacted by the size of the project.